Evaluasi Program Pendidikan Islam Terintegrasi di Emmer Islamic Boarding School: Pendekatan Model CIPP - Suryaningtiyas Puspa Wardhani; Windi Widianti; Yetri Yetri; Ahmad Fauzan (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2026)
This study aims to evaluate the implementation of the integrated Islamic education program at Emmer Islamic Boarding School (EIBOS) using the CIPP (Context, Input, Process, Product) evaluation model. The research approach used was descriptive qualitative with an evaluative approach. Data collection techniques included in-depth interviews, observation, and documentation studies. The results showed that: (1) contextually, the Islamic education program at EIBOS is relevant to the needs of students in the global and digital era; (2) from an input perspective, the availability of human resources, an integrated curriculum, and educational technology support meet the standards for modern Islamic education; (3) from a process perspective, the implementation of learning and boarding school guidance is integrated and sustainable; and (4) from a product perspective, the program has a positive impact on the development of students' religious character, independence, and digital literacy. The CIPP model has proven effective as an evaluation instrument for Islamic education programs and can be used as a basis for decision-making in developing the quality of sustainable education at Islamic Boarding Schools.